2016
DOI: 10.1021/jacs.6b07227
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Resonance Vibrational Spectroscopic Definition of Peroxy Intermediates in Nonheme Iron Sites

Abstract: FeIII-(hydro)peroxy intermediates have been isolated in two classes of mononuclear non-heme Fe enzymes that are important in bioremediation: the Rieske dioxygenases and the extradiol dioxygenases. The binding mode and protonation state of the peroxide moieties in these intermediates are not well defined, due to a lack of vibrational structural data. Nuclear resonance vibrational spectroscopy (NRVS) is an important technique for obtaining vibrational information on these and other intermediates, as it is sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Due to its isotope sensitivity, the 510 cm −1 feature can be assigned as the νFe−O. Qualitatively, based on a previous NRVS study on high-spin Fe III − (hydro)peroxy models, 50 the peaks centered at 277 cm −1 are equatorial Fe−N His stretches. This previous study showed that the energy of the νFe−O and the splitting between equatorial Fe−N stretches are sensitive to the coordination mode of O 2 and its protonation state.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its isotope sensitivity, the 510 cm −1 feature can be assigned as the νFe−O. Qualitatively, based on a previous NRVS study on high-spin Fe III − (hydro)peroxy models, 50 the peaks centered at 277 cm −1 are equatorial Fe−N His stretches. This previous study showed that the energy of the νFe−O and the splitting between equatorial Fe−N stretches are sensitive to the coordination mode of O 2 and its protonation state.…”
Section: Results and Analysismentioning
confidence: 99%
“…49 To calibrate our DFT method for BZDOp and define the binding mode and protonation state of high-spin Fe III –(hydro)peroxy models, we previously analyzed NRVS data on a side-on Fe III –peroxy model 10 and an end-on Fe III –hydroperoxy model 10 (both high-spin and ligated by the 4-coordinate 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane (TMC) ligand). 50 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides non-Rieske [2Fe2S] 22 and [3Fe4S] 23 proteins and [4Fe4S] 24 proteins, It is important to note that 57 Fe NRVS has been expanded to study electron transfer in larger enzymes and their catalytic metallocofactors such as (but not comprehensively) the NiFe site in [NiFe] hydrogenase, 3, 2526 the diiron site in [FeFe] hydrogenase, 2728 the P [8Fe7S]- and M [7Fe9SMo]- clusters of Mo-Nitrogenase, 2932 heme systems, 3334 non-heme systems, 3536 and nitric-oxide sensing [4Fe4S] clusters. 37 Further as the systems of interest have become more complicated, with multiple FeS clusters of differing composition, innovative strategies of site-specific 57 Fe labeling have been implemented that target maturation 28 or a modified cofactor insertion.…”
Section: Perspectivementioning
confidence: 99%